Врските помеѓу Македонија и Хрватска во средниот век - Атанасовски, Александар (Завод за заштита на спомениците на културата и Музеј, Струмица, 2017)
To speak of the relations between Macedonia and Croatia in the Middle Ages, is to talk about a topic that is unique and complicated in many ways. In encompasses several issues, such as cultural, military, political and trade relations, as well as often scarcely documented relationships between individuals. The mutual ties from the early Middle Ages, even those of later times, present a rather serious problem, which comes from the fact that mediaeval Macedonia was under foreign domination, so the connections took place within the bounds of the relations of Byzantium, Bulgaria and Serbia with Croatia. On the other hand, the territory of today’s Croatia in the Middle Ages was not always within the borders of a single state. Parts of it belonged to Pannonia, the Adriatic coast was under Byzantine rule, and then, after 1102, it came under Hungarian rule. Dubrovnik existed as an independent state, being the state with which Macedonia had the most fertile trade relations. Considering the above, it becomes obvious why it is difficult to talk about unified communications between Macedonia and Croatia. We are able, however, to present the links of various Croatian territories and lands with Macedonia. We encompass the cultural and educational ties, reflected through the missionary work of St. Cyril and Methodius in Moravia and Panonia; the military and political contacts at the time of Samuel’s state; and, eventually, the commercial connections of Dubrovnik with Macedonia in XIII and XIV century.
Links between Macedonia and Croatia in the Middle Ages